A Review on Malaysian Women’s Leisure and Perceptions Towards Solo Travelling. - Wahidin Awang, Khairil; Ying Toh, Jen (International Journal of Engineering and Technology, 2018)
The female travel market has shown an increase in leisure travel especially in Asia. Global travel is meant for men in the past but the women travel phenomenon has gradually emerged. Malaysia is among the South East Asian countries which is experiencing a sturdy growth in tourism. The aim of this study is to explore Malaysian women viewpoints towards solo travelling. This study addresses the activeness of Malaysian women in leisure and provides an insight of these women from the Asian perspective.  A qualitative approach is employed in this study. Malaysia is a pluralist country and thus it would be ideal to understand the country’s social and cultural influences on women’s perception of solo travel. Data is collected among Malaysian women aged from 19 to 33 years old. An in-depth interview technique is conducted to identify the perceptions of Malaysian women on solo travelling and subsequently the travelling patterns. The findings indicate that the women possessed positive determination in overcoming the constraints of solo travelling. Furthermore, the individuals’ social and cultural identities do not restrict them not to take leisure travel. However, Malaysian women prefer to travel in groups instead of solo travel. This paper provides academicians, tourism marketers and policymakers with a glimpse of Asian perspectives, particularly of Malaysian women and solo travelling, and hence can better prepare the industry in tapping the lucrative solo travelling market.